2019
DOI: 10.3390/su11154110
|View full text |Cite
|
Sign up to set email alerts
|

Which Diet Has the Least Environmental Impact on Our Planet? A Systematic Review of Vegan, Vegetarian and Omnivorous Diets

Abstract: The food that we consume has a large impact on our environment. The impact varies significantly between different diets. The aim of this systematic review is to address the question: Which diet has the least environmental impact on our planet? A comparison of a vegan, vegetarian and omnivorous diets. This systematic review is based on 16 studies and 18 reviews. The included studies were selected by focusing directly on environmental impacts of human diets. Four electronic bibliographic databases, PubMed, Medli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
127
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(159 citation statements)
references
References 36 publications
7
127
0
3
Order By: Relevance
“…Founded in 2014, the company aims to become a major fashion accessory player, but with the differential of being a vegan and sustainable brand. It is widely believed today that vegan diets have a positive impact on the environment [104]. However, despite the vegan world being well known in the food industry, it is still emerging and not well understood by the general population in other segments such as the clothing and accessories industries.…”
Section: The Selected Companymentioning
confidence: 99%
“…Founded in 2014, the company aims to become a major fashion accessory player, but with the differential of being a vegan and sustainable brand. It is widely believed today that vegan diets have a positive impact on the environment [104]. However, despite the vegan world being well known in the food industry, it is still emerging and not well understood by the general population in other segments such as the clothing and accessories industries.…”
Section: The Selected Companymentioning
confidence: 99%
“…To reduce these environmental burdens, profound changes in the food system are needed, including a shift towards environmentally sustainable diets [1]. These are often regarded as diets causing lower environmental impacts (e.g., [5]), which several studies have identified as diets with a low to moderate amount of meat and animal-based products and a larger share of plant-based Sustainability 2020, 12, 1407 2 of 22 foods than in current diets in many high-income countries [6][7][8][9]. This conclusion was also reached by Martin and Brandão [10], who investigated implications of dietary changes by the Swedish population.…”
Section: Introductionmentioning
confidence: 99%
“…According to research by Chai et al, the dietary patterns of vegetarians, non-vegetarians, and omnivores have different effects on the environment [62]. Therefore, in the following discussion, combined with demographic scenario analysis and different diet patterns, it is more scientific to judge which diet has the least impact on the environment of our planet, so as to make reasonable adjustments to the improvement of the dietary structure.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%